ESTIMASI KEBUTUHAN BIAYA INVESTASI UNTUK PEMBANGUNAN KAWASAN PERBATASAN ANTARNEGARA - Alkadri, Alkadri (Badan Pengkajian dan Penerapan Teknologi, 2007)
The development of many aspects in most regencies/municipalities in cross-border area is left behind, compare with the development archieve in other regions inIndonesia. Indeed, cross-border area have an important role as a front gate (main entrance) of Indonesia. This phenomenon happened because of the limitted budget for cross-border area development. This budget allocation is smaller than the actually budget needed for increasing the cross-border area development. Using economic growth approach and fiscal capacities approach of every region, this paper estimates the investment needed for development in eight region of crossborder areas during 2006-2009.